Difficult analysis of the deployment of the operator’s SD-WAN - Jiong GU (Dianxin kexue)
Through analyzing the deployment method of Google SD-WAN on its B4 network and how it help users reduce the WAN’s expenditure and enhance its own WAN connection flexibility,a SD-WAN model of the application of the domestic WAN was established.Through analyzing the feasibility of the application of SD-WAN in our country,a good way to applicate SD-WAN as “sharing network” in IDC was proposed.